2004
DOI: 10.1021/bc049962b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Poly(amidoamine) Dendrimers with Supported Lipid Bilayers and Cells:  Hole Formation and the Relation to Transport

Abstract: We have investigated poly(amidoamine) (PAMAM) dendrimer interactions with supported 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) lipid bilayers and KB and Rat2 cell membranes using atomic force microscopy (AFM), enzyme assays, flow cell cytometry, and fluorescence microscopy. Amine-terminated generation 7 (G7) PAMAM dendrimers (10-100 nM) were observed to form holes of 15-40 nm in diameter in aqueous, supported lipid bilayers. G5 amine-terminated dendrimers did not initiate hole formation but expanded ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

72
677
0
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 574 publications
(756 citation statements)
references
References 24 publications
72
677
0
7
Order By: Relevance
“…The former mechanism can lead to cell death due to loss of membrane polarization and/or leakage of ions and molecules into/out of the cell. To establish whether 'striped' nanoparticles penetrate cell membranes through creation of transient holes, we tested whether the internalization of ligand-protected nanoparticles was accompanied by escape of cytosol-localized tracer dye or conversely, cytosolic entry of an initially extracellular tracer dye 41,42 . First, DC2.4 cells were co-incubated with nanoparticles and calcein; calcein remains in endolysosomal compartments in cells unless it is co-internalized with a membrane-disrupting agent 43 .…”
mentioning
confidence: 99%
“…The former mechanism can lead to cell death due to loss of membrane polarization and/or leakage of ions and molecules into/out of the cell. To establish whether 'striped' nanoparticles penetrate cell membranes through creation of transient holes, we tested whether the internalization of ligand-protected nanoparticles was accompanied by escape of cytosol-localized tracer dye or conversely, cytosolic entry of an initially extracellular tracer dye 41,42 . First, DC2.4 cells were co-incubated with nanoparticles and calcein; calcein remains in endolysosomal compartments in cells unless it is co-internalized with a membrane-disrupting agent 43 .…”
mentioning
confidence: 99%
“…This observation was similar to the ndings reported in previous numerical and experimental studies of the interactions between an un-acetylated G5 dendrimer and a DPPC lipid bilayer, 18 a DMPC lipid bilayer 33 and cell membranes (KB and Rat2). 34 The experimental results indicated that the pore formation during the interactions of the dendrimer-DMPC lipid bilayer was caused by the removal of lipid molecules from the supported substrate by the dendrimers, resulting in a composite of dendrimers and lipids. 33 During the inner interaction, similar to the G4 dendrimer, the G5 dendrimer was also adsorbed tightly onto the inner leaet of the membrane.…”
Section: Interactions Between the G5 Dendrimer And Asymmetric Membranesmentioning
confidence: 96%
“…10,12,27 In addition, the degree of membrane disruption parallels the degree of nonselective tissue uptake observed in vivo. 29 This correlation between the AFM/SLB assays and the in vitro and in vivo studies inspired us to examine the disruption between other nanoparticles that are well precedented to disrupt and/or translocate across cell membranes.…”
mentioning
confidence: 92%